Internet-induced marketing techniques: Critical factors in viral marketing campaigns - Maria Woerndl; Savvas Papagiannidis; Michael Bourlakis; Feng Li (International Journal of Business Science & Applied Management (IJBSAM), 2008)
The rapid diffusion of the Internet and the emergence of various social constructs facilitated by Internet technologies are changing the drivers that define how marketing techniques are developed and refined. This paper identifies critical factors for viral marketing, an Internet-based 'word-of-mouth' marketing technique. Based on existing knowledge, five types of viral marketing factors that may critically influence the success of viral marketing campaigns are identified. These factors are the overall structure of the campaign, the characteristics of the product or service, the content of the message, the characteristics of the diffusion and, the peer-to-peer information conduit. The paper discusses three examples of viral marketing campaigns and identifies the specific factors in each case that influence its success. The paper concludes with a viral marketing typology differentiating between viral marketing communications, unintended viral marketing and commercial viral marketing. This is still a rapidly evolving area and further research is clearly needed to monitor new developments and make sense of the radical changes these developments bring to the market.
Keywords: 650; viral marketing; marketing campaigns; internet word-of-mouth; social networking